Effect Of Different Coolant Medium On Warpage Deflection Using Moldflow Insight Analysis - Mohd Amran, Md Ali; Siti Salmah, Mohd Sani; Zulkeflee, Abdullah; Liew, Pay Jun; Mohd Razali, Muhamad; Raja Izamshah , Raja Abdullah; Mohd Hadzley, Abu Bakar; Abu , Abdullah; Zolkarnain, Marjom (Trans Tech Publications, 2015)
The effect of mould temperature on warpage using water and oil as coolant fluid was studied using flow software analysis. Mould temperature was controlled using two types of coolants; where cold mould was controlled by water and hot mould was controlled by oil. The simulation analysis was performed using flow software analysis Moldflow Plastics Insight (MPI). Taguchi method was used to design the planning matrix and to find the optimum levels of input variables. Then, to find the percentage contribution of input variables on output variables, analysis of variance (ANOVA) was used. It is found that mould temperature controlled by water shows less warpage analysis compared to oil. The minimum and maximum percentage of warpage analysis between cold mould and hot mould are 3.1% and 7.1% respectively. In addition, ANOVA analysis shows that the most significant parameters affected the warpage analysis for both moulds using oil and water are melt temperature (255°C) followed by mould temperature (water 15°C and oil 70°C) and cooling time (water 8s and oil 6s). Thus, it shows that coolant medium used in mould cooling system contributes the quality of plastic parts.